2016
DOI: 10.33549/physiolres.933187
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Alveolar Macrophages Attenuates Hypoxic Pulmonary Hypertension but not Hypoxia-Induced Increase in Serum Concentration of MCP-1

Abstract: Exposure to hypoxia, leading to hypoxic pulmonary hypertension (HPH), is associated with activation of alveolar macrophages (AM). However, it remains unclear how AM participate in this process. There are studies which imply that the AM product monocyte chemoattractant protein-1 (MCP-1) plays an important role. Thus we tested: 1. if the selective elimination of AM attenuates HPH in rats, 2. the correlation of MCP-1 plasmatic concentrations with the presence and absence of AM during exposure to hypoxia, 3. the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In contrast to the progressive expansion of interstitial macrophages, we found that alveolar macrophages were decreased in both rodent and human instances of PH. To our knowledge, alveolar macrophages have not previously been quantified in depth in human PH, but other groups have conversely reported their increase [72] and activation [73] in chronically hypoxic mice. These discrepancies may be explained by a recent report delineating a spatio-temporal program of at times divergent alveolar and interstitial macrophage activation in hypoxic lungs of mice [21].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the progressive expansion of interstitial macrophages, we found that alveolar macrophages were decreased in both rodent and human instances of PH. To our knowledge, alveolar macrophages have not previously been quantified in depth in human PH, but other groups have conversely reported their increase [72] and activation [73] in chronically hypoxic mice. These discrepancies may be explained by a recent report delineating a spatio-temporal program of at times divergent alveolar and interstitial macrophage activation in hypoxic lungs of mice [21].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions targeting macrophages have confirmed their role in PAH and pulmonary vascular remodeling. An intratracheal depletion of alveolar macrophages with liposome-encapsulated clodronate attenuated the increase in pulmonary arterial pressure in response to chronic hypoxia in rats [ 82 ]. Furthermore, the depletion of macrophages normalized the increase in RVSP seen in BMPR2 knockout mice exposed to chronic hypoxia [ 83 ].…”
Section: Inflammatory Mediators and Their Effects On Vascular Remomentioning
confidence: 99%
“…Moreover, the depletion of recruited monocytes with gadolinium chloride in neonatal hyperoxia-exposed rats demonstrated reduced RVH and decreased SMC proliferation [ 34 ]. Recently, Zaloudikova et al demonstrated that depletion of alveolar macrophages attenuates hypoxic PH, emphasizing the role of pulmonary macrophages in PH pathogenesis [ 35 ]. Like pulmonary resident macrophages, myeloid-derived suppressor cells (MDSCs) are a different type of myeloid cell with immuno-modulatory activity.…”
Section: Macrophage-mediated Immunity In Pahmentioning
confidence: 99%